De Garengeot’s Hernia: Two Case Reports with Correct Preoperative Identification of the Vermiform Appendix in the Hernia - Zhaosheng Jin; Muhammad Rafiz Imtiaz; Henry Nnajiuba; Suzette Samlalsingh; Akinyede Ojo (Case Reports in Surgery)
We present two cases of incarcerated de Garengeot’s hernia. This anatomical phenomenon is thought to occur in as few as 0.5% of femoral hernia cases and is a rare cause of acute appendicitis. Risk factors include a long pelvic appendix, abnormal embryological bowel rotation, and a large mobile caecum. In earlier reports operative treatment invariably involves simultaneous appendicectomy and femoral hernia repair. Both patients were correctly diagnosed preoperatively with computed tomography (CT). Both had open femoral hernia repair, one with appendectomy and one with the appendix left in situ. Both patients recovered without complications. Routine diagnostic imaging modalities such as ultrasonography and standard CT have previously shown little success in identifying de Garengeot’s hernia preoperatively. We believe this to be the first documented case of CT with concurrent oral and intravenous contrast being used to confidently and correctly diagnose de Garengeot’s hernia prior to surgery. We hope that this case report adds to the growing literature on this condition, which will ultimately allow for more detailed case-control studies and systematic reviews in order to establish gold-standard diagnostic studies and optimal surgical management in future.